Modelling road transport technologies in future scenarios: Theoretical comparison and application of Well-to-Wheels and Input-Output analyses. (15th December 2018) - Rocco, Matteo V.; Casalegno, Andrea; Colombo, Emanuela
Highlights: Input-Output analysis is proposed to perform LCA of future automotive technologies. Input-Output analysis and Well-to-Wheels methods are theoretically compared. Penetration of fuel cell vehicles in Germany in 2050 has modelled and analyzed. Results of Input-Output analysis are significantly different compared to Well-to-Wheels. Abstract: According to IEA projections, the penetration of electric vehicles in the world transportation sector is expected to increase in the next decades to comply with the future GHG emissions policy targets. The change in transport technology mix will cause a change the environmental and economic impacts of the transportation sector, switching it from flows to funds, that is, from the production and use of the fuel to the production of the fuel pathway and powertrain infrastructures. Therefore, due to their comprehensiveness, the use of Life Cycle Assessment models will be increasingly important with respect to Well-to-Wheels ones in assessing the impact of future transport technologies. In this paper, the Hybrid Input-Output analysis is proposed as the appropriate framework to assess the impact due to a change in transport technology mix from a LCA perspective. First, LCA and WTW approaches are theoretically compared. Secondly, the LCA model is applied for the analysis of the economic and environmental impact caused by the prospected penetration of Fuel Cell Electric Vehicles (FCEV) based on Proton Exchange Membrane Fuel Cell (PEMFC) for Germany in 2050. In addition to the production of the vehicles, the LCA model includes the infrastructures for hydrogen production and distribution and the prospected change in the national electricity production mix. Significant discrepancies have been found by comparing results of LCA with the ones obtained by well-established WTW models already available in the literature. It is found that the impact caused by infrastructures and production of vehicles could significantly offset the expected reduction in CO2 emissions and primary non-renewable energy consumptions.